Помогите решить все пожалуйста
![](https://files.topotvet.com/i/469/469cf7eb8b3049854caee70cad0367cc.jpg)
Ответы
Ответ:
62)
64)
66)
68)
70)
72)
74)
78)
Ответ:
Объяснение:
2y/(5a) +a⁴/(2y)=(2y·2y+5a·a⁴)/(5a·2y)=(4y²+5a)/(10ay)
(3z-8)/(5z²) +(z-1)/z²=(3z-8+5(z-1))/(5z²)=(3z-8+5z-5)/(5z²)=(8z-13)/(5z²)
(2a+3b)/(21ab) +(a-6b)/(15ab)=(2a+3b)/(3·7ab) +(a-6b)/(3·5ab)=5(2a+3b)/(5·21ab) +7(a-6b)/(7·15ab)=(10a+15b+7a-42b)/(105ab)=(17a-27b)/(105ab)
2/(a-5) +5/(2a-10)=2/(a-5) +5/(2(a-5))=(2·2+5)/(2(a-5))=(4+5)/(2a-10))=9/(2a-10)
2/(a+5) +3/(a+2)=(2(a+2)+3(a+5))/((a+5)(a+2))=(2a+4+3a+15)/(a²+2a+5a+10)=(5a+19)/(a²+7a+10)
(y-x)/(x(x-a)) +(a-y)/(a(x-a))=(a(y-x)+x(a-y))/(ax(x-a))=(ay-ax+ax-xy)/(ax(x-a))=(ay-xy)/(ax(x-a))=y(a-x)/(-ax(a-x))=-y/(ax)
2b/(1-b²) +1/(1+b)=2b/((1-b)(1+b)) +1/(1+b)=(2b+1-b)/((1-b)(1+b))=(b+1)/((1-b)(b+1))=1/(1-b)
a/(a+b)² +1/(a+b)=a/((a+b)(a+b)) +1/(a+b)=(a+a+b)/(a+b)²=(2a+b)/(a+b)²=(2a+b)/(a²+2ab+b²)